ANALYSIS OF AGE, BODY MASS INDEX, AND MENTAL WORKLOAD TOWARDS COMPLAINTS OF FATIGUE DURING PANDEMIC COVID-19 IN PRIMARY HEALTH CARE - Dian Puspitaningtyas Laksana (Poltekkes Kemenkes Malang, 2022)
The Puskesmas is the first health facility for the surrounding community, especially North Semarang. Health center workers on duty have high work demands, especially during the covid-19 pandemic. High work demands can cause fatigue. Work fatigue is a condition that leads to a weakening of activities, motivation, and an increased mental load. This study describes several factors related to complaints of subjective fatigue in health and non-health workers at the puskesmas—analytical research using a cross-sectional approach. The study was conducted on 43 research respondents who met the inclusion criteria. Data was collected using a questionnaire and the Spearman rank test to determine the relationship between age, body mass index, and mental workload with complaints of fatigue. The results showed that the research respondents were 38 years old on average, with a normal body mass index, and had a moderate workload and mild to reasonable fatigue complaints. The results showed no significant relationship between age, body mass index, and mental workload. Fatigue management is needed to help reduce fatigue in the workplace, starting with